Pulpektomi satu kali kunjungan denganRestorasi onlay komposit pada gigi premolar dan molar rahang atas - Stefani, Rosita; Subrata, Aryadi; Melaniwati; Tjingson, Natalia; Steward (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: The main aim of endodontic treatment is to eliminate bacterial infection in the pulp and to preserve treated teeth in their best condition, restoring the structure and function of healthy teeth. Dental clinicians should be aware that both adequate root canal treatment and post-treatment restoration work in unison to achieve a successful endodontic treatment.  Objective: The purpose of this article is to demonstrate pulpectomy as an endodontic treatment choice for upper premolar and molar permanent teeth with the diagnosis of irreversible pulpitis, followed by the placement of composite onlay on both teeth.  Case report: A 38-year-old woman sought treatment at RSGM-P Universitas Trisakti, complaining of persistent food trapping in her upper left teeth, which contributed to halitosis. The patient noted episodes of throbbing pain associated with those teeth for three months. Intra-oral examination showed a moderate to large cavity on tooth 25 and 26, both reaching the pulp, as confirmed by radiographic examination. At the first visit, pulpectomy was performed on tooth 26 from caries removal, access opening, irrigation, pulp extirpation, artificial wall building with GIC, biomechanical preparation, and obturation. Patient was told to come again one week after to get the same treatment on 25. At her third visit, composite onlay preparation was conducted. After finished, dental impression of tooth 25 and 26 was carried out to be proceed on laboratory. Cementation was scheduled to one week after on the next visit using resin cement. Patient revisited for follow-up after one month of placement with no complaints. Conclusion: One visit pulpectomy was succesfully carried out on tooth 25 and 26 followed by composite onlay restoration.